Propagation, Establishment, and Early Fruit Production of Table Grape Microvines in an LED‐Lit Hydroponics System: A Demonstration Case Study - E. S. Malai; C. A. O'Sullivan; T. J. Grant; L. Sreekantan; V. A. Mellor; S. Schmidt; I. B. Dry (Plant-Environment Interactions)
ABSTRACT Controlled environment farming (CEF) systems, including tunnel houses, glasshouses, and vertical farms, are expanding worldwide. As the industry scales, growers need a broader range of crops that are adapted to CEF systems to take full advantage of the potential to increase yields and decrease weather‐related risks. Dwarf grapevines (microvines) are ideal candidates for CEF due to their high economic value, phenotype, and phenology. This study aimed to develop propagation protocols, a critical first step for the successful integration of microvines in the CEF market, and to demonstrate the establishment, early growth, first flowering, and fruiting of table grape microvines in a fully indoor, LED‐lit, CEF system. An experiment was conducted to investigate the efficiency of clonal propagation of a newly developed microvine variety, which had been bred for the production of seedless table grapes in response to two variables: (a) shoot position of cutting, and (b) length of time of misting exposure (from 3 to 7 weeks). A subset of successfully established plantlets were then transplanted into a hydroponic, CEF system, where their establishment, early growth, flowering, and fruit formation were assessed. Three weeks after cuttings were taken, 83.7% of the cuttings had formed roots, regardless of cutting section or misting treatment, while the remaining 16.7% of cuttings died. The sprouting success was lower with 49.3% of plants forming new leaves after 7 weeks. The highest level of sprouting was observed with cuttings taken from mid‐shoot and lower shoot positions and the 5‐week misting duration. While the rooting efficiency and survival of green shoot microvine cuttings are very high, further research is needed to increase the frequency of sprouting in the required timeframes to levels that are more acceptable for commercial production. The establishment success of sprouted cuttings after transplanting to hydroponics was 100% and their production and fruit quality were similar regardless of cutting tissue source. The crop cycle from planting to first harvest was 208 days (63 days for plantlet production and 145 days from transplanting to first harvest). The vines began flowering after an average of 33.9 days and the berries went through veraison (i.e., commencement of ripening) after an average of 116 days under the conditions tested. Microvine fruit grown under these conditions contained greater than the minimum total soluble solids content required for the Australian market. We have demonstrated that table grape microvines have potential as a novel crop for CEF systems.